Efisiensi Pakan Larva Ikan Nila (Oreochromis Niloticus) Hasil Maskulinisasi Madu Hutan - Muhammad Amri Yusuf; Rahmi Fitrawati; Annisa Annisa; Rahayu Abriani Sahar; Reza Gustiyani Ayu (Yayasan Literasi Sains Indonesia, 2024)
Nile tilapia is a superior commodity that has been developed with high production. Male nile tilapia has a growth rate of 2 times faster than female nile tilapia, so the cultivation of male nile tilapia (monosex) is far more profitable. The masculinization using honey will produce monosexual male nile tilapia, through immersion method using honey. Honey contain flavonoids which function to direct male genitals. Honey also contains potassium which triggers steroid hormones in protein metabolism, brings glucose into cells and stimulates the hypothalamus, so that it can trigger appetite in animals and influence the level of consumption and feed efficiency. This study aims to determine the best type of honey in nile tilapia larvae for consumption and feed efficiency. Honey used in this study were; forest honey (from Bontocani, Selayar, Sumbawa) and livestock honey with a dose of 0.2% of the total volume of solvents, through the immersion method. The seven days old nile tilapia larvae were immersed in the treatments for 24 hours, then they were reared for 60 days. Completely Randomized Design (CRD) with 3 replications per treatment was used in this experiment. The results showed that honey from Bontocani forest produced highest feed consumption and forest honey (from Bontocani, Selayar and Sumbawa) produced highest feed efficiency.